Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1038/s41598-018-33611-8
|View full text |Cite
|
Sign up to set email alerts
|

Low abundance of sharks and rays in baited remote underwater video surveys in the Arabian Gulf

Abstract: Data on the diversity and relative abundance of elasmobranchs (sharks and rays) in the Arabian Gulf have been limited to fishery-dependent monitoring of landing sites. Understanding the diversity and abundance of sharks and rays is, however, crucial to inform policy and management plans. Baited Remote Underwater Video Surveys (BRUVS) were conducted in 2015–2016 across the United Arab Emirates Arabian Gulf waters encompassing a range of depths and habitat types. Data from 278 BRUVS (757 hours soak time) were an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Underwater cameras of different types and levels of technological advancements have been used with increasing frequency to further research in long-term monitoring of the environment [9], in situ behavior observations of deep-water species [10], abundance surveys, including sharks and rays [11], fish habitat monitoring [12], and in fish farming net cage applications [13]. Valuable information has also been obtained using underwater cameras in studies related to commercial fishing gear, including fish and crab behavior with trawls and seines [14][15][16][17], and efficiency of catch with longlines [18].…”
Section: Introductionmentioning
confidence: 99%
“…Underwater cameras of different types and levels of technological advancements have been used with increasing frequency to further research in long-term monitoring of the environment [9], in situ behavior observations of deep-water species [10], abundance surveys, including sharks and rays [11], fish habitat monitoring [12], and in fish farming net cage applications [13]. Valuable information has also been obtained using underwater cameras in studies related to commercial fishing gear, including fish and crab behavior with trawls and seines [14][15][16][17], and efficiency of catch with longlines [18].…”
Section: Introductionmentioning
confidence: 99%
“…Giant guitarfishes and wedgefishes reside preferentially in soft bottom areas of coral reefs and seagrass meadows. Their flattened body is adapted to the benthos, and they mostly swim close to the sea floor or lie concealed within sea‐bed sediments (Oh, 2016; Jabado et al, 2018a). However, these habitats face losses and fragmentation effects due to overfishing, pollution, and climate change (Wear, 2016; Unsworth et al, 2018), severely threatening giant guitarfishes and wedgefishes in their natural environment (Jabado et al, 2017; Kyne et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…When sold fresh, these elasmobranchs can fetch a relatively high price of US$4 per kilogram (Choy CPP & Choo MY, 2020, unpublished data), and a whole wedgefish over 2 m in total length can be sold at prices as high as US$680 (Jabado, 2018) owing to its reputation as good quality meat (Moore, 2017). Together, artisanal and commercial fisheries put extreme pressure on harvested populations (Last, White & Pogonoski, 2008; Dulvy et al, 2014; Jabado et al, 2018a; D'Alberto et al, 2019), with declining catch rates in trawl surveys and reductions in landings reported at fishing ports across the Indo‐West Pacific and Indian Ocean despite a substantial increase in fishing effort (Jabado et al, 2018b). Indeed, the most recent global assessment based on the International Union for Conservation of Nature (IUCN) Red List Categories and Criteria (IUCN, 2012) indicates that all species except the eyebrow wedgefish, Rhynchobatus palpebratus , have undergone >80% population decline over the last 30–45 years and are classified as Critically Endangered (Kyne et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The use of baited remote underwater video stations (BRUVS) is perhaps one of the most accessible, highly replicated, non-destructive and effective tool for quantifying fish assemblages, species-habitat associations and anthropogenic impacts across large spatial scales 19,22,23 . Using bait increases the probability of detecting predators in the environment, since the resulting bait plume can trigger bait-search behaviors in nearby species 24,25 .…”
mentioning
confidence: 99%